Effect of changes in climate variables on hydrological regime of Chenab basin, western Himalaya. Issue 1 (27th April 2021) - Grover, Sonia; Tayal, Shresth; Sharma, Richa; Beldring, Stein
Abstract: In high altitude, scarcely gauged basins, climate change impact assessment on river discharge is important for sustainable management of water resources. These basins are sources for irrigation and hydropower generation in the region. Expected changes in precipitation and temperature can affect the basin's hydrological regime which will have consequential impacts on the dependent sectors. For quantifying the impacts of major climatic variables on hydrological processes, this paper examined bias-corrected GCM outputs coupled with a hydrological model – HBV for Chenab basin. Trend analysis shows that precipitation would decrease after the short-term period and temperature is expected to increase throughout the century. Simulated river discharge is expected to increase throughout the 21st century under both RCP 4.5 and RCP 8.5 scenarios. It is also observed that there would be a shift in seasonal discharge patterns with increased pre- and post-monsoon contributions. Increase in snow and ice melt contribution to the overall discharge is also expected and would range between 50 and 59% until 2100. This study concluded that expected increase in discharge volume coupled with shift in seasonal discharge pattern would impact the basin water management and thus it is important to consider the impact of climate change on the hydrological regimes of basins. HIGHLIGHTS: Paper deals with the ungauged basin originating from the Himalayas and assesses shifts in seasonal discharge patterns which highlights increased pre- and post- monsoon contributions in annual discharge. Output from the study is important for the data scarce Himalayan region and for better planning and management of water resources. Graphical Abstract